In Situ Formed Tribofilms as Efficient Organic/Inorganic Hybrid Interlayers for Stabilizing Lithium Metal Anodes - Huang, Shaozhen; Long, Kecheng; Chen, Yuejiao; Naren, Tuoya; Qing, Piao; Ji, Xiaobo; Wei, Weifeng; Wu, Zhibin; Chen, Libao (Nano-Micro Letters, 2023)
The practical application of Li metal anodes (LMAs) is limited by uncontrolled dendrite growth and side reactions. Herein, we propose a new friction-induced strategy to produce high-performance thin Li anode (Li@CFO). By virtue of the in situ friction reaction between fluoropolymer grease and Li strips during rolling, a robust organic/inorganic hybrid interlayer (lithiophilic LiF/LiC6 framework hybridized -CF2-O-CF2- chains) was formed atop Li metal. The derived interface contributes to reversible Li plating/stripping behaviors by mitigating side reactions and decreasing the solvation degree at the interface. The Li@CFO||Li@CFO symmetrical cell exhibits a remarkable lifespan for 5,600 h (1.0 mA cm−2 and 1.0 mAh cm−2) and 1,350 cycles even at a harsh condition (18.0 mA cm−2 and 3.0 mAh cm−2). When paired with high-loading LiFePO4 cathodes, the full cell lasts over 450 cycles at 1C with a high-capacity retention of 99.9%. This work provides a new friction-induced strategy for producing high-performance thin LMAs. Highlights: 1 The robust organic/inorganic hybrid interlayer derived from in situ formed tribofilms were fabricated by using a scalable rolling method. 2 The interlayer facilitates dendrite-free lithium metal anodes by building local de-solvation environments near the interface and inhibiting both dendrite growth and electrolytes corrosion. 3 The symmetrical cell exhibits a remarkable lifespan of 5,600 h (1.0 mA cm-2 and 1.0 mAh cm-2) and 1,350 cycles even at a harsh condition (18.0 mA cm-2 and 3.0 mAh cm-2).